2016
DOI: 10.1039/c5cc08956e
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature methoxylation in zeolites: insight into a key step of the methanol-to-hydrocarbons process

Abstract: Neutron scattering methods observed complete room temperature conversion of methanol to framework methoxy in a commercial sample of methanol-to-hydrocarbons (MTH) catalyst H-ZSM-5, evidenced by methanol immobility and vibrational spectra matched by ab initio calculations. No methoxylation was observed in a commercial HY sample, attributed to the dealumination involved in high silica HY synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 46 publications
7
81
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have also been used to model the diffusion of alkanes into MFI zeolites, as measured by means of QENS and neutron spin‐echo (NSE) . Methanol diffusion (QENS), reaction, and adsorption (INS) during the methanol‐to‐hydrocarbon process have also been studied …”
Section: Hydrogen Interactions With Oxide Catalystsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have also been used to model the diffusion of alkanes into MFI zeolites, as measured by means of QENS and neutron spin‐echo (NSE) . Methanol diffusion (QENS), reaction, and adsorption (INS) during the methanol‐to‐hydrocarbon process have also been studied …”
Section: Hydrogen Interactions With Oxide Catalystsmentioning
confidence: 99%
“…The resulting ex situ spectra unambiguously reveal the presence of hydrocarbon species, which may be associated with a hydrocarbon pool. Whereas O'Malley et al [28] concentrated on methanol exposure to ZSM-5 at room temperature, this communication describes an investigation performed at reaction temperatures representative of those utilised in MTG unit operations. Thus, INS is being used here to assess how hydrogen is partitioned within the catalyst matrix during conditions that correspond to the commercially relevant active phase of MTG operation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ability of INS to selectively probe hydrogeneous vibrational modes [15], it is enticing to discover whether the technique can provide new information on the adsorbed hydrocarbon species present at various stages of the methanol to hydrocarbon reaction. Very recently, O'Malley et al [28] have used a combination of neutron scattering methods matched by ab initio calculations to investigate, amongst other things, the reaction of methanol with ZSM-5 at room temperature. That study showed methanol to be immobilized due to methoxylation, and that the formation of adsorbed methoxy groups is facile over this material at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[19] This technique has previously synergized well with other in situ characterization tools to better understand many catalytic processes. [20] We therefore present, for the first time, a combined in situ FTIR and QENS study on SAPO-34. We aim to integrate knowledge of the specific interactions of the reaction mechanism, with understanding of the structureproperty relationships, which dictate the diffusive motion of the organic moieties.…”
Section: Introductionmentioning
confidence: 99%